Nature under siege: An ecocritical reading of Bahar Dutt’s Green Wars - Thakur, Ram Sebak; Singh, Ajita; Sharma, Priyanka (Rajarshi Janak University Research Journal, 2025)
The paper aims to present a comprehensive study of the ecocritical dimensions of Bahar Dutt's Green Wars: Dispatches from a Vanishing World (2014). Dutt's account of her journey, presented in the form of a chronicle of piquant stories and anecdotes in the course of environmental journalism, comes out as a splendid narrative highlighting her environmental advocacy. Undertaking the ecocritical stance, this research analyses how, in the name of development, Nature is rampantly abused, degraded, and destroyed. The text under study addresses the emerging issues of biodiversity conservation by critiquing the unsustainable rubrics sanctioned by the Indian State Government, contributing to drastic and irreparable deterioration of ecology. Dutt's investigative journalism forecasts the environmental apocalypse, and mirrors her eco-anxiety. The study applies a qualitative research design, emphasizing and interpreting the quotations and anecdotes from the text replete with ecological concerns. The textual analysis is done through the lens of ecocriticism, thereby foregrounding the universal environmental problems ranging from the extinction of certain flora and fauna, melting of glaciers, to the mindless infrastructural development causing pollution and ecological imbalance.